2006
DOI: 10.1007/s10554-006-9092-9
|View full text |Cite
|
Sign up to set email alerts
|

Dedicated calibration formulas permit correction of differences between measurements by different IVUS devices as demonstrated in atherosclerotic human coronary arteries in vitro

Abstract: Serial intravascular ultrasound (IVUS) measurements of coronary vessel dimensions are major endpoints of studies focusing on pharmacological interventions, efficiency of drug eluting stents, and vascular remodeling. In serial studies measurement variability among different IVUS devices may cause substantial misinterpretation and error. We analyzed 33 human coronary plaques in vitro using two different IVUS systems (mechanical IVUS system with a 40 MHz Atlantis SR catheter; solid-state electronic IVUS system wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…The number of coronary segments was limited but comparable to other studies that addressed the reproducibility of IVUS measurements [1315, 34, 38, 39]. All patients had stable angina pectoris.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The number of coronary segments was limited but comparable to other studies that addressed the reproducibility of IVUS measurements [1315, 34, 38, 39]. All patients had stable angina pectoris.…”
Section: Discussionsupporting
confidence: 53%
“…Therefore, measurement reproducibility may be somewhat lower in routine clinical IVUS cases; nevertheless, the selection criteria of target segments in serial IVUS studies are similar [710]. Inter-catheter and inter-system variability was not addressed [34, 38, 39]. The high accuracy of the off-line RF-IVUS analysis was achieved at the expense of manual correction of the automatically derived lumen and vessel contours; accordingly, our data may not be generalized to on-line application of RF-IVUS.…”
Section: Discussionmentioning
confidence: 99%
“…We do believe that IVUSderived measurements are accurate and reproducible. However, early studies demonstrated discrepancies in quantitative results between different IVUS systems [9][10][11]. An in vitro study comparing between 40 MHz mechanical IVUS (Atlantis SR/Ultracross, Boston Scientific) and 20 MHz phased array IVUS (InVision/Avanar, Volcano, Rancho Cordova, CA, USA) demonstrated up to 18% differences in quantitative results between the 2 systems [9].…”
Section: Discussionmentioning
confidence: 99%
“…Intravascular ultrasound (IVUS) is widely used to guide percutaneous coronary intervention (PCI) [1][2][3][4][5] and to assess efficacy of medication or PCI on coronary atherosclerotic plaque or stent in vivo [6][7][8]. Previously, there were discordance in quantitative measurements of the coronary arteries using different IVUS systems from different providers mainly because of the differences in the speed of sound used in each IVUS system [9][10][11]. The aim of this study was to assess compatibility of two different IVUS catheters and consoles for quantitative measurements of coronary arteries.…”
Section: Introductionmentioning
confidence: 99%
“…The data of this study do not predict whether a reduction of image density may introduce an additional measurement variability (for instance when data are sampled at a pullback speed of 1.0 mm/s instead of 0.5 mm/s). In serial studies, [33] potential variability between different IVUS catheters or IVUS systems may add to the overall measurement variability of RF–IVUS studies [34]. …”
Section: Discussionmentioning
confidence: 99%